SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN UNIT PELAYANAN TEKNIS BALAI KONSERVASI TUMBUHAN KEBUN RAYA PURWODADI LEMBAGA ILMU PENGETAHUAN INDONESIA BERBASIS WEB - Apriyanto, Heri; ., Sujito; Dwi Mumpuni, Indah (DINAMIKA DOTCOM, 2017)
Purwodadi Botanical Garden still experiencing problems in the record, manage and search for employment data collections because all process still use the file storage vaults. This makes data management processes are not well structured and search the data or employee file will take quite a long time. Related issues such as personnel administration data calculation error on leave, the absence of a history of the award, punishment, education, seminars and so on can be one of the obstacles and constraints to the development of human resources well. Based on these problems need for Development of Human Resources Management Information System that can help record, manage and help search history data from the incoming employee as ID until his retirement in digital form so as to minimize errors that can be wrong an obstacle in the development of Human Resources. Type of research is descriptive research, the type of data used are primary and secondary data, engineering data collection is by interview and observation. For analysis method the author uses descriptive method where data is collected, compiled, interpreted, and analyzed so as to provide complete information on the problems encountered. For application development, the method used is the System Development Life Cycle (SDLC). This method has the phases of planning, analysis, design, implementation and maintenance of the system.Keywords: Information System, Human Resources Development, Purwodadi Botanical Garden